605 STEPWISE APPROACH TO ROBOTIC SURGERY IN A HIGH-VOLUME CENTER WITHOUT PREVIOUS EXPERIENCE IN ROBOTIC ESOPHAGEAL SURGERY. (14th September 2020) - Riva, P; Pansa, A; Da Roit, A; Basato, S; Marano, S; Castoro, C
Abstract:  : Minimally Invasive esophagectomy has been introduced to reduce the trauma associated with open surgery while keeping the same oncological outcome. Robotic platforms could facilitate this. Even with the increasing availability of surgical robots and the standardization of the technique, it can be difficult to convince high volume centers to change their surgical approach. Our aim is to assess the impact of the learning curve for robotic surgery in a high-volume laparoscopic center. Methods: We retrospectively analyzed a prospectively collected database in a tertiary referral center for esophagogastric surgery. We identified two groups composed by the patients who underwent Ivor-Lewis (IL) esophagectomy by a hybrid laparoscopic (HL) approach (standard laparoscopy + open thoracotomy) and those who underwent a hybrid robotic (HR) approach (robotic abdominal part + open thoracotomy) with the Davinci Xi surgical platform for lower esophageal or EGJ cancer from November 2018 to September 2019. Data regarding post-operative stay, complications, leaks, total number of lymph nodes and length of surgery were analyzed. Complications were reported according to the ECCG classification. Results: We selected 50 consecutive IL cases among which there were our first 17 HR cases. There were no differences in terms of demographics, comorbidities and neoadjuvant treatments between the two groups. No statistical difference was observed in post-operative stay(median 12 vs 10 days in HL and HR respectively, p = 0.09), overall complication rate was 33% in HL and 35% in HR(p = 0.9), patients with leaks 1(3.03%) in HL and 1(5.88%) in HR(p = 0.6), total lymph nodes median of 38 in HL vs 30 in HR(p = 0.4). Only the total length of surgery was statistically longer in the HR group (median 446 vs 478 min, p = 0.01). Conclusion: We showed that in the setting of a high-volume center with no previous robotic surgery expertise, robotically performing only the abdominal phase could represent an effective alternative to familiarize with the robotic system without compromising the clinical outcome and workflow. We understand that the main advantages would be seen when using the robot during the thoracic part. After these first cases we will proceed to adopt it during the most demanding part of the operation.